Komunikasi Organisasi Dalam Mengoptimalkan Kinerja dan Disiplin Kerja Karyawan di PT. Alfa Scorpii Sentral Yamaha Medan - Armanda Nul Azmi (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
Organizational communication is an important factor in a company because it plays a role in conveying information, coordinating work, and establishing working relationships between leaders and employees that can affect work performance and discipline. This study aims to determine the role of organizational communication in optimizing employee work performance and discipline at PT. Alfa Scorpii Sentral Yamaha Medan. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation with six informants consisting of one supervisor and five employees selected using purposive sampling. The results of the study indicate that organizational communication is carried out through work briefings, internal meetings, and digital communication media such as WhatsApp groups to convey information and work instructions. Employee work performance and discipline are generally classified as good, as seen from the ability of employees to achieve work targets and compliance with working hours and standard operating procedures (SOPs). Thus, organizational communication plays an important role in improving employee work performance and discipline.